Rural tourism: a case of Cameron Highlands, Pahang. The relationship between service quality & tourist loyalty towards tourist experience as mediator / Alif Azhari Ismail, Norhidayah Mohd Yusoff and Mohammad Izzul Hanis Abdul Rahman - Ismail, Alif Azhari; Mohd Yusoff, Norhidayah; Abdul Rahman, Mohammad Izzul Hanis (2015)
This paper examined tourists’ evaluation of service quality in rural tourism destination, which is in Cameron Highlands, Pahang, Malaysia. Cameron Highlands is a highland, which is quite popular among tourists that want to see yet another side of Malaysia; a side where they can walk for hours in the cool climate. Because of the perfect climate, it was very suitable for cultivating tea; Cameron Highlands soon grew out to be the biggest tea region of Malaysia and one of the top rural tourism destinations. The domestic tourists’ experience acts as the mediating effect of domestic tourists’ loyalty on this relationship. The data was analysed using multi-regression method. The service quality dimensions delivered have a significant positive influence on tourists’ loyalty. Moreover, previous experience moderates the relationship between service quality and domestic tourists’ loyalty. The findings of this study offer some interesting implications for practitioners and researchers.